Diksi Kelam dalam Kumpulan Puisi Antologi Mimpi Karya Anna N. A. F.: Kajian Stilistika - Angger Gilang Praditama; Andi Elsa Fadhilah Sakti (Universitas Muhammadiyah Kotabumi, 2026)
This study aims to describe the use of dark-toned diction in the poetry collection Antologi Mimpi by Anna N. A. F. (2017). The study employs a qualitative descriptive method with a stylistic approach to examine the use of language in constructing meaning and aesthetic effects in poetry. The research data consist of quotations of words, phrases, and sentences containing dark-toned diction found in the poetry collection. Data were collected through intensive reading techniques and note-taking of diction that represents a gloomy emotional atmosphere. The data were analyzed using an interactive analysis technique, which includes data condensation, data presentation, and conclusion drawing. The findings reveal that dark diction in Antologi Mimpi represents psychological human conditions, including helplessness, despair, and emotional entrapment caused by memories of past romantic relationships. The use of metaphors, symbols, and imagery associated with wounds, emptiness, and illusory hope strengthens the emotional intensity of the poems and enhances readers’ affective engagement. The findings confirm that diction in poetry functions not only as an aesthetic element but also as a medium for representing the poet’s inner experiences, which are universal in nature. Therefore, a stylistic analysis of dark diction can reveal the relationship between language choice, emotional expression, and meaning construction in literary works.